ChemInform Abstract: Synthesis and Catalytic Activities of Porphyrin‐Based PCP Pincer Complexes. Issue 31 (5th August 2014) - Fujimoto, Keisuke; Yoneda, Tomoki; Yorimitsu, Hideki; Osuka, Atsuhiro
Abstract Peripherically metalated porphyrin phosphine pincer complexes are developed and their catalytic activity is demonstrated for the allylation of benzaldehyde with allylstannane.